Wheat potassium transporter TaHAK13 mediates K+ absorption and maintains potassium homeostasis under low potassium stress - Run, Yonghang; Cheng, Xiyong; Dou, Wei; Dong, Yue; Zhang, Yanan; Li, Bingbing; Liu, Tengfei; Xu, Haixia (Frontiers in Plant Science, 2022)
ABSTRACT: Potassium (K) is an essential nutrient for plant physiological processes. Members of the HAK/KUP/KT gene family act as potassium transporters, and the family plays an important role in potassium uptake and utilization in plants. In this study, the TaHAK13 gene was cloned from wheat and its function characterized. Real-time quantitative PCR (RT-qPCR) revealed that TaHAK13 expression was induced by environmental stress and up-regulated under drought (PEG6000), low potassium (LK), and salt (NaCl) stress. GUS staining indicated that TaHAK13 was mainly expressed in the leaf veins, stems, and root tips in Arabidopsis thaliana, and expression varied with developmental stage. TaHAK13 mediated K+ absorption when heterologously expressed in yeast strains, and its transporter activity was slightly stronger than that of a TaHAK1 positive control. A subcellular localization analysis illustrated that TaHAK13 was located to the plasma membrane. When c(K+) ≤0.01 mM, the root length and fresh weight of TaHAK13 transgenic lines (athak5/TaHAK13, Col/TaHAK13) were significantly higher than those of non-transgenic lines (athak5, Col); the net K influx of the transgenic lines was also higher than that of the non-transgenic lines. This suggests that TaHAK13 promotes K+ absorption, especially in low potassium media. Membrane-based yeast two-hybrid (MbY2H) and luciferase complementation assays (LCA) showed that TaHAK13 interacted with TaNPF5.10 and TaNPF6.3.